DISEASE IDENTIFICATION IN TEAK (Tectona grandis) AND ACACIA (Acacia auriculiformis) IN COMMUNITY FOREST OF WONOGIRI DISTRICT CENTRAL JAVA - Burhan Ismail; Illa Anggraeni (Jurnal Pemuliaan Tanaman Hutan, 2008)
Since the regreening project launched by presidential decree in 1976/1977 and the movement of National Land Forest Rehabilitation (GNRHL) in 2003, community forest plantation area is increasing and inclined to be more independent in their plantation management. In Wonogiri district the community forest achieve the total area of 27.433 hectare, spreaded out in 25 subdistricts. Disease on forest plantation is one of factors that causing significant risk and has to be tackled seriously. The odjective is to identify plant disease (particularly on Teak and Acacia) in community forest of Wonogiri district, Central Java. This is a preliminary study to determine further strategy in disease management. The result showed that teak plants were attacked by bacteria of Pseudomonas tectonae (Ralstonia solanacearum). While Acacia were attacked by fungi of Meliola sp., Atelocauda digitata and Oidium sp., the three fungus attacked Acacia are obligate parasitic.